Characterization, Purification and Antiserum Production of Sweet Potato Feathery Mottle Potyvirus (SPFMV) - Ahmad, Khairulmazmi (2003)
Characterization, purification and production of antiserum against sweet potato feathery mottle potyvirus (SPFMV) were carried out in this study. Characterization of the virus involved host range reaction, inclusion bodies determination, virion morphology and determination of coat protein molecular mass. Initial serological detection of potyviruses infection was carried-out by Indirect ELISA using an Agdia® commercial kit for potyvirus on samples of sweet potato collected from major growing areas in Peninsular Malaysia, Sabah and Sarawak. Experimental results of this study showed, potyviruses are present in most of the major sweet potato growing areas in Peninsular Malaysia and some areas in Sabah and Sarawak. The SPFMV isolate used in this study was single probed by aphid and vectored to healthy Ipomoea setosa three times. The initial infection symptom on I. setosa was characterized by veinal chlorosis of actively growing leaves. In subsequent leaves, the veinal chlorosis was concentrated to major veins. Progressively the veinal chlorosis was restricted to midvein. Subsequent new foliar growth was symptomless. Host reaction results showed, I. nil produced symptoms of faint vein clearing and crinkling after inoculation. Symptomless I. purpurea tested positive in Indirect ELISA, thus showing latent infection in this host. The rest of the indicator plants did not show any virus symptom and tested negative in the ELISA test. These results indicated that the virus isolate in this study has a narrow host range and restricted to the Convolvulaceae family only. Cytoplasmic inclusions (Cis), a major characteristic of the poty group, were observed under light microscopy. In the infected cells, the Cis were stained dark blue (Azure A) and were usually located beside the plant cell nuclei.